Bioactive glass: A potential next generation biomaterial - Srishti Sarin; Amit Rekhi (Wolters Kluwer Medknow Publications, 2016)
Historically the function of biomaterials has been to replace diseased or damaged tissues. The first generation biomaterials were selected to be as bio-inert as possible and thereby minimize formation of scar tissue at the interface with host tissues. Bioactive glasses (BAGs) were discovered in 1969 and provided for the first time an alternative; the second generation, interfacial bonding of an implant with host tissues. Tissue regeneration and repair using the gene activation properties of Bioglass® provide a third generation of biomaterials. This article reviews the history of the development of BAGs, with emphasis on the first composition, 45S5 Bioglass®, that has been in clinical use since 1985. A bioactive ceramic is a ceramic that generate a positive reaction in the biological environment of the implants and/or chemical reaction that modify the material in a certain thickness under the surface.